Zum Beitrag von Oliver Bruttel (ZAF 1/2005, "Die Privatisierung der öffentlichen Arbeitsvermittlung: Erfahrungen aus Australien, den Niederlanden und Großbritannien") - Regina Konle-Seidl (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– Other countries have already privatised their job placement systems to a greater extent than Germany has. This concerns such different welfare state regimes as Australia and Great Britain on the one hand and the Netherlands - and more recently also Belgium and Denmark - on the other hand. According to Bruttel the experiences made in other countries have shown that a stronger role of private employment agencies is to be assessed positively. He therefore suggests testing this method for Germany without prejudice. The aim of this paper is to discuss the preconditions for a successful 'privatisation' of employment services and to evaluate the experiences made by other countries when 'privatising' their employment services. In particular it is discussed whether extensive 'contracting out' of placement and integration services is a desirable alternative to the current restructuring of the Federal Employment Agency (Bundesagentur für Arbeit) from a 'bureaucracy to a modern client-oriented service provider'. The following questions form the crux of the paper: (1) Are internal PES reforms aimed at increasing the effectiveness and efficiency per se inferior to the 'privatisation option'? (2) Is there solid information about whether a 'privatised' system is superior to public employment services irrespective of the particular labour market context and its specific problems? (3) How far should 'privatisation' go and what factors promote its success? On the whole the paper reaches a rather cautious evaluation of the 'privatisation gains' expected by Bruttel.
Keywords: 330; Arbeitsvermittlung; Privatisierung - internationaler Vergleich; private Arbeitsvermittlung - Effizienz; Australien; Niederlande; Großbritannien